Non invasive Management of Post Dural Puncture Headache - A Comparison (Bangladesh Journal of Medical Science, 2014)
Aim: To evaluate the efficacy of oral Theophylline for the management of post dural puncture headache (PDPH). Material and Method: Forty patients with PDPH, whose surgeries were done under spinal anaesthesia, were selected randomly and divided into two groups of 20 each. One group to receive conservative treatment and the other group Theophylline (400 mg) only orally. Intensity of headache was analysed using a visual analogue scale (VAS) of pain. Assessment was done immediately before (0 h) and at 8, 16 and 24th hr of drug administration. Result: Significantly better relief of PDPH was found in Theophylline (9.3±5.7) than the conservative group (56.7 ±10.2) (p